2019
DOI: 10.3390/cells8060603
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Micronutrients in the Infection and Subsequent Response to Hepatitis C Virus

Abstract: Micronutrient deficiencies develop for a variety of reasons, whether geographic, socioeconomic, nutritional, or as a result of disease pathologies such as chronic viral infection. As micronutrients are essential for a strong immune response, deficiencies can significantly dampen both the innate and the adaptive arms of antiviral immunity. The innate immune response in particular is crucial to protect against hepatitis C virus (HCV), a hepatotropic virus that maintains chronic infection in up to 80% of individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 164 publications
0
70
0
7
Order By: Relevance
“…Vitamins A, B complex, C, D, and E and many trace elements, such as iron, zinc, selenium, magnesium, and copper, have been shown to elicit immune-boosting properties, 14–16 and thus deficiencies of these micronutrients could be detrimental to immune function in viral infections. 17 Likewise, supplementing diets with micronutrients has been reported as a way to improve or optimize immune function against viral infections; therefore, public health officials must consider nutritional interventions as a means to combat emerging viral infections. 6 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Vitamins A, B complex, C, D, and E and many trace elements, such as iron, zinc, selenium, magnesium, and copper, have been shown to elicit immune-boosting properties, 14–16 and thus deficiencies of these micronutrients could be detrimental to immune function in viral infections. 17 Likewise, supplementing diets with micronutrients has been reported as a way to improve or optimize immune function against viral infections; therefore, public health officials must consider nutritional interventions as a means to combat emerging viral infections. 6 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been carried out in patients with some chronic viral infections, like HBV, HCV, and HIV. These trials have shown the following in chronically infected patients: (a) serum concentrations of vitamins A, E, D and C are decreased [72,73], (b) vitamins A, D, E and C deficiency is associated with higher levels of viral replication as well as with higher titers of pro-inflammatory cytokines, like IL-6 and TNF-α, or with illness severity in some studies carried out in different virus-associated diseases [72][73][74][75][76][77][78][79], (c) vitamins may suppress or reduce viral replication or load in different virus infections both in adults and in children [80][81][82][83][84].…”
Section: The Current Knowledge On the Possible Activity Of The Liposomentioning
confidence: 99%
“…The inhibitory roles of these essential trace elements are revealed in the translation, transcription, and replication of hepatitis viruses, including hepatitis B virus (HBV), hepatitis C virus (HCV), and hepatitis E virus (HEV). Se and Zn were demonstrated to suppress the transcription and replication of hepatitis viruses [ 8 , 9 ]. Table 1 shows the function of such trace elements in the translation, transcription, and replication of these viruses.…”
Section: The Roles Of Trace Elementsmentioning
confidence: 99%